WHICH EDUCATIONAL DANCE PROGRAMS CAN BE USED TO IDENTIFY CHILDREN’S TALENTS - Elindra Yetti; Erie Siti Syarah; Ayu Niza Machfauzia (Jurnal Cakrawala Pendidikan, 2021)
Education will be more meaningful if it is in accordance with children's talents and development. If talents can be recognized from an early age, it will be easier for children to reach the gates of success. This study aims to discuss educational dance programs that facilitate the identification of early childhood dance talents. This study used a qualitative method with data collection through observation, interviews, video documents, and reflection journals. The study was conducted on fifteen students aged 5-6 years in a kindergarten in the Special Capital Region of Jakarta. Findings of the study show that educational dance activity programs can make it easier for teachers and parents to identify early childhood dance talents. The audio-visual activities in the process of exploring dance movements make it easier for teachers and parents to identify early childhood dance talents compared to other movement stimuli. New approach to identify children's dance talents that can be used as a guide by teachers and parents in identifying and developing children's dance talents from an early age.